O teletrabalho e a gaiola de silício: autonomia, controle e resistência no contexto da pandemia de Covid-19 - Veloso, Braian Garrito (Universidade Federal de São Carlos, 2025)
This research has, as a general objective, to analyze the trends in new processes of technification of contemporary life revealed from the experience of transition from face-to-face work to teleworking in the context of the Covid-19 pandemic. We start from the hypothesis that this experience of change is fertile ground for observing the main characteristics that involve the relationships between workers and digital technologies within a specific historical-social framework that, in this thesis, we defend based on the original concept called silicon cage. The specific objectives are: to describe and define the characteristics of teleworking, considering its specificities in the context of the Covid-19 pandemic; identify the objective conditions of teleworking in the context of the pandemic and beyond of it; understand the relationship between workers and digital technologies and the resulting implications; investigate changes from face-to-face work to teleworking based on modulations of time, space and subjective engagement in light of the perception and experience of autonomy; and explain the transition from the iron cage to the silicon cage. When it comes to methodology, it is a qualitative approach that included convenience sampling. The study starts from a phenomenological perspective in that it emphasizes the subjects' experience and their perceptions. Regarding methodological procedures, we used: narrative bibliographic review, virtual questionnaire and semi-structured interviews. Based on some of the main results, it was observed that, in the pandemic, the relationship between workers and technologies involved, in some cases, important resignifications in the ways in which subjects understand digital technological resources; the experiences of teleworkers during the pandemic are also related to previous objective conditions; modulations in teleworking, when combining time and space, tend to promote overload situations; and the use of mobile technologies contributes to the configuration of what we call the silicon cage as a process of technification of contemporary life.

Esta investigación tiene como objetivo general analizar las tendencias de los nuevos procesos de tecnificación de la vida contemporánea que se revelan a partir de la experiencia de transición del trabajo presencial al teletrabajo en el contexto de la pandemia Covid-19. Partimos de la hipótesis de que esta experiencia de cambio es un terreno fértil para observar las principales características que involucran las relaciones entre trabajadores y tecnologías digitales dentro de un marco histórico-social específico que, en esta tesis, defendemos a partir del concepto original llamado jaula de silicio. Los objetivos específicos son: describir y definir las características del teletrabajo, considerando sus especificidades en el contexto de la pandemia Covid-19; identificar las condiciones objetivas del teletrabajo en el contexto de la pandemia y más allá de ella; comprender la relación entre los trabajadores y las tecnologías digitales y las implicaciones resultantes; investigar los cambios del trabajo presencial al teletrabajo a partir de modulaciones del tiempo, el espacio y el compromiso subjetivo a la luz de la percepción y experiencia de la autonomía; y explique la transición de la jaula de hierro a la jaula de silicio. En cuanto a la metodología, se trata de un enfoque cualitativo que incluyó un muestreo por conveniencia. El estudio parte de una perspectiva fenomenológica en la que enfatiza la experiencia de los sujetos y sus percepciones. En cuanto a los procedimientos metodológicos, utilizamos: revisión bibliográfica narrativa, cuestionario virtual y entrevistas semiestructuradas. A partir de algunos de los principales resultados, se observó que, en la pandemia, la relación entre trabajadores y tecnologías implicó, en algunos casos, importantes resignificaciones en las formas en que los sujetos entienden los recursos tecnológicos digitales; las experiencias de los teletrabajadores durante la pandemia también se relacionan con condiciones objetivas previas; las modulaciones en el teletrabajo, al combinar tiempo y espacio, suelen favorecer situaciones de sobrecarga; y el uso de tecnologías móviles contribuye a la configuración de lo que llamamos jaula de silicio como un proceso de tecnificación de la vida contemporánea.
Teleworking and the silicon cage: autonomy, control and resistance in the context of the Covid-19 pandemic
Teletrabajo y la jaula de silicio: autonomía, control y resistencia en el contexto de la pandemia de Covid-19
Keywords: Tecnologias Digitais; Teletrabalho; Pandemia; Digital technologies; Telework; Pandemic; Tecnologías digitales; Teletrabajo; Pandemia; CIENCIAS HUMANAS::SOCIOLOGIA